The evolutionary economic geography of climate change - Hogarth, J (2015)
The evolutionary economic geography of climate change is concerned with the processes by which the landscapes of greenhouse gas emissions and vulnerability to climate change are transformed from within over time. Unlike neoclassical economics, evolutionary economic geography is interested in how economic change is driven by innovation and shaped by structural, historical, and contextual factors at different scales. This thesis articulates an evolutionary economic geography perspective on three debates: (1) What factors influence human systems’ capacity to adapt to climate change, and how can these factors be assessed? (2) What forces drive and inhibit economic change towards low-carbon economies, and how should governments induce and manage such shifts? (3) What role should climate finance play in promoting developing countries’ shifts to low-emitting and climate-resilient economies, and how should it be managed? The thesis includes five academic papers. The first reviews the literature on vulnerability and adaptation. It argues that the adaptive capacity of human systems is constrained by structural and historical factors, and that the rich data necessary to identify these factors can only be obtained through qualitative research methods. The next two papers offer case studies from the Global Islands’ Vulnerability Research Adaptation and Policy Development project, which assess the adaptive capacity of Soufriere, Saint Lucia and Whitehouse, Jamaica, respectively. The fourth paper examines the mechanics of three low-carbon shifts in Brazil: the diffusion of no-till agriculture, the decrease in the deforestation rate in the Amazon, and the growth of the ethanol biofuel industry. It found that the driving forces behind each of the shifts were far more varied and complex than the price-based market dynamics analysed in neoclassical economics. The final paper argues that climate finance will need to perform a variety of functions beyond attracting low-carbon private investment. It concludes that the institutional architecture governing climate finance should enable direct access to national governments to incentivise them to implement sustainable innovation policy regimes.